PTH-097 Notch1 is a master regulator of the senescence secretome through repression of c/ebpΒ. (22nd June 2015) - Hoare, M; Ito, Y; Kang, T-W; Menon, S; Salama, R; Zender, L; Narita, M
Abstract : Introduction: Oncogene-induced senescence (OIS) is an intrinsic tumour suppressor mechanism, but its impact on tumorigenesis is largely dependent on the nature of SASP, senescence-associated secretory phenotype. Major components of the SASP include TGFβ1 and pro-inflammatory cytokines, such as IL1A, IL6, and IL8 that have pleiotropic context-dependent effects. Method: We utilised the well validated ER:Ras G12V IMR90 HDF in vitro model which undergo Ras-induced senescence (RIS) with 4OHT. In vivo hepatocyte RIS was achieved with hydrodynamic tail-vein injection of NRas G12V -containing transposons. Results: Previously, we have shown that Notch1, a highly conserved receptor is up-regulated in RIS. In contrast to the up-regulation of Notch1, downstream signalling is dynamically regulated; Notch-target genes were transiently up-regulated at an early phase of RIS, but down-regulated at full senescence. The dynamic expression pattern of N1ICD and TGF-β1 expression were nearly identical, and inversely correlated with the cytokines, IL1A and IL8. Inhibition of Notch1 signalling, through expression of a dominant-negative form of the Notch1 binding partner MAML1, led to a reduction in TGF-β1, but increased IL1A and IL8 expression during RIS, suggesting Notch1 signalling plays a critical role in secretome switching. It has been shown that the SASP in RIS is regulated by two major transcription factors, NFkB and CEBPβ. Strikingly, over-expression of N1ICD strongly down-regulated CEBPβ, but not NFkB, in fully established RIS cells. Further, expression of ectopic CEBPβ in N1ICD-expressing cells partially restored levels of IL6/8. N1ICD was also able to suppress pro-inflammatory cytokine expression in TNF-α stimulated cells, through repression of CEBPβ. These data indicate that Notch1 represses pro-inflammatory cytokines by down-regulating CEBPβ. Finally, Notch1 up-regulation in OIS was confirmed in Nras-driven hepatocyte senescence; Notch1 inhibition through dnMAML1 promoted immune-mediated clearance of senescent hepatocytes. Conclusion: We propose that the transition to OIS is correlated with a switch from Notch1-driven TGFβ-rich secretome to a CEBPβ-driven IL1/8 rich secretome, and that dynamic Notch1 signalling modulates senescence and its long-term fate strictly through a non-cell-autonomous fashion. Disclosure of interest: None Declared.